읽기이해부진 학생을 위한 읽기중재 연구 동향 - 고선희(Sunhee Ko) (특수교육논총, 2020)
연구목적: 읽기는 새로운 지식을 습득하기 위한 필수적인 수단이며, 특히 학령기 아동들에게는 학업성취를 위한 핵심 기술이기에 읽기이해부진 아동들을 위한 중재 연구는 지속적으로 이루어질 필요가 있다. 이에 본 연구에서는 읽기이해부진 아동들을 대상으로 실시한 중재 연구들을 고찰해 봄으로써 국내 연구 동향을 살펴보고, 앞으로의 연구 방향을 모색해 보고자 하였다. 연구방법: 국내에서 읽기이해 중재를 실시한 연구들을 선정하여 연구대상 특성, 중재한 글의 유형, 글 유형에 따른 중재 전략을 중심으로 분석하였다. 연구 결과: 대부분의 연구에서 초등학생을 대상으로 읽기이해 중재 연구를 실시하였다. 읽기이해부진을 진단하기 위해 대다수의 연구에서 지능, 읽기이해, 학업성취도 검사를 실시하였는데 아동들의 음독 능력을 평가하지 않은 연구가 상당 수 확인되었다. 읽기이해를 중재하기 위해 사용된 글의 유형은 설명글, 이야기글, 복합유형글로 고르게 분포하였는데 설명글에서는 그래픽조직자, 요약하기, 상보적 글읽기 전략, 이야기글에서는 그래픽조직자와 이야기문법교수 전략이 높은 빈도로 사용되었다. 결론: 연구 결과로 볼 때 추후의 연구에서는 보다 다양한 연령대의 아동들을 대상으로 읽기이해 중재가 이루어져야 할 것이며, 글의 유형에 따라 중재 전략이 달라질 수 있기에 연구 목적에 맞는 글의 종류를 선택할 필요가 있을 것이다. 또한 음독 능력의 수준에 따라 읽기 중재 목표가 달라질 수 있기 때문에 읽기이해부진 아동을 진단할 때 음독 수준을 반드시 확인할 필요가 있을 것이다. Purpose: Reading is essential in acquiring new knowledge, as well as a key academic skill among school-aged children. For this reason, intervention studies for children with poor reading comprehension are crucial. Thus, this study aimed to analyze the trends in domestic research and seeking directions for future research by examining the intervention studies conducted on children with poor reading comprehension in Korea. Method: The research analyzed primarily focused on the characteristics of the study subject, the type of texts, and the intervention strategies according to the text type. Results: First, elementary students were main participants in most of the studies. Second, intelligence, reading comprehension, and academic achievement tests were administered in most of the studies to detect children with poor reading comprehension; however, some studies did not evaluate children’s decoding skills. Third, the types of texts for reading comprehension intervention were evenly distributed into the expository, narrative, and mixed texts. In expository texts, graphic organizers, summarizing, and complementary reading strategies were applied at a high rate; in narrative texts, graphic organizers and story grammar strategies were applied at a high rate. Conclusion: Intervention for children spanning a wider age range in the future is required. As the intervention strategy may vary depending on the type of text, it is essential to select the type of text that suits the study purpose. In addition, checking decoding skills when diagnosing children with poor reading comprehension is necessary. KCI Citation Count: 5